2016
DOI: 10.1155/2016/7354018
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A Level in Egyptian Children with Familial Mediterranean Fever

Abstract: Background and Objectives. SAA is an acute-phase reactant detected during an FMF attack or other inflammatory conditions. High SAA levels may increase the risk of amyloidosis. The aim of the study is to measure the serum amyloid A (SAA) level in a group of Egyptian children with familial Mediterranean fever (FMF) and study its various correlates, if any. Methods. The study enrolled seventy-one children with FMF. Results. SAA level was high in 78.9% of the studied patients with a mean of 81.62 ± 31.6 mg/L, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
11
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
6
11
1
1
Order By: Relevance
“…The most frequent MEFV gene mutations were V726A (24.35%), E148Q (20.87%), M694I (20.43%), M680I (12.61%), M694V (10.43%), and A7445 (3.04%). This is nearly similar to many studies [26,27] while in the study by Mneimneh et al [28], M694V (37.2%) and E148Q (27.4%) were the commonest. These differences may be due to the effect of different genetic backgrounds that affect the genetic pattern of the disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The most frequent MEFV gene mutations were V726A (24.35%), E148Q (20.87%), M694I (20.43%), M680I (12.61%), M694V (10.43%), and A7445 (3.04%). This is nearly similar to many studies [26,27] while in the study by Mneimneh et al [28], M694V (37.2%) and E148Q (27.4%) were the commonest. These differences may be due to the effect of different genetic backgrounds that affect the genetic pattern of the disease.…”
Section: Discussionsupporting
confidence: 90%
“…When we analyzed the clinical presentation, we found that abdominal pain was the most common followed by fever, chest pain, and arthritis. This is similar to the results of another Egyptian study [26], while Duşunsel et al [27] reported that fever was the most common followed by abdominal pain. It seems that different genetic patterns of the disease among different populations affect the clinical picture of the attacks.…”
Section: Discussionsupporting
confidence: 89%
“…The levels of S100A12 and resolvin D correlated significantly (p < 0.001) with the classical inflammatory biomarkers as 70 (89.7%) patients had high serum amyloid levels, which agree with Lofty et al 28 and Duzova et al 29 Similarly, Ben-Zvi and Livneh 24 affirmed that although the Fig. 3 The ROC curve of S100A12 and resolvin D1 was at a cutoff point of 529.5 pg/mL and 231 pg/mL respectively, their sensitivity was 97.4 and 100%, specificity 80 and 50% respectively and the areas under the curve (AUC) was 0.958 and 0.82 respectively.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, CRP was elevated in 50 (64.1%) cases higher than the findings of others studies. 28,29,32 The number of patients with increased SAA was more than those with elevated CRP. This may be due to the high sensitivity of SAA in detecting the degree of inflammation.…”
Section: Discussionmentioning
confidence: 97%
“…[ 40 ] 2017 Aktive Erkrankung trotz mindestens 3 Monate langer Kolchizin-Therapie Lofty, H.M. et al. [ 41 ] 2016 ≥1 Attacke/Monat Melikoglu, M.A. et al.…”
mentioning
confidence: 99%